EFEKTIVITAS DAUN GAMBIR ( UNCARIA GAMBIR ROXB ) UNTUK MENURUNKAN HALITOSIS YANG DISEBABKAN OLEH PLAK Studi di Panti Asuhan dan Pondok Pesantren Zuhriyah, Sleman, Yogyakarta - Irfan Irfan; Yayun Siti Rochmah; Moh Yusuf; Grahita Aditya (ODONTO : Dental Journal, 2015)
Introduction: Halitosis is the smell of bad breath that comes out of the mouth. Gambir contained catechins which is a material that helps in inhibited bacteria and VSC (Volatic Sulfur Compound) as the cause of halitosis.Purpose: The aim of research to assess the effectiveness of gambir leaves against halitosis is caused by plaque.Methods: The method in this research is pre experimental research with 18 research subjects students. Halitosis parameter measurements made before and after the use of gambir for 3 days. VSC gas is measured using the tool "Oralchroma". Statistical data processing is done with the Wilcoxon test (p <0.05 as significant level).Results: There were decreased levels in each of the gas before and after gargling on treatment. H2S levels down to 100%, CH3SH fell by 43%, (CH3)2S down 24%. The three gas is visible gas reduction percentage is the highest H2S and the lowest is (CH3)2S. Wilcoxon test results obtained H2S sig 0.109 (p <0.05), CH3SH sig 0.005 (p <0.05) and (CH3)2S sig 0.009 (p <0.05).Conclusion: Gambir leaf decoction is effective against halitosis is caused by plaque.